ANALYSIS OF INTERNATIONAL EXPERIENCE IN ENSURING THE TRANSPARENCY (OPENNESS) OF STATE POLICY REGARDING YOUTH - Yuldasheva Khusnida Jumanazar qizi (Galaxy International Interdisciplinary Research Journal, 2024)
Ensuring the openness and transparency of the activities of state power institutions in foreign countries has developed in a unique way. In developed foreign countries, special legal documents have been adopted that regulate the processes of citizens receiving information about the activities of state authorities, and the processes of presenting laws and other normative documents to the public. The process of ensuring that the state power institutions provide information about their activities to the public is regulated, and this is one of the important functions of the state. In many foreign countries, the government is obliged by law to ensure the free access of citizens to information about the activities of state power institutions. Quick and accurate delivery of information, information and documents related to state activities to the public.